DECISIONS AND ACTIONS OF NURSING CARE GROUNDED IN THE THEORY OF MADELEINE LEININGER - Susanne Elero Betiolli; Dâmarys Kohlbeck de Melo Neu; Marineli Joaquim Meier; Marilene Loewen Wall; Maria Helena Lenardt (Universidade Federal do Paraná, 2013)
The present study aimed to identify decisions and actions in nursing used in Brazilian scientific productions grounded in the Madeleine Leininger's Theory of Universality and Diversity of Cultural Care, which proposes that the nurse should use the decisions and actions of care for undertaking culturally congruent nursing care. It is an integrative review, with a sample of 12 scientific productions, from the analysis of which emerged two themes: utilization of the modes of care; and reference to the modes of care. The modes of preservation, accommodation and re-standardization of care were identified, the decisions and actions of accommodation being studied with greater emphasis by the authors. In spite of the small quantity of scientific productions, it is emphasized that the same allow the identification of decisions and actions of care, in addition to detecting their applicability in the nurse's practice, as well as their adaptation in the search for satisfactory care for the clients